Nosemosis negatively affects honeybee survival: experimental and meta-analytic evidence - Monika Ostap-Chec; Jessica Cait; R. Wilder Scott; Aneta Arct; Dawid Moroń; Marcin Rapacz; Krzysztof Miler (Parasitology)
Nosemosis, caused by microsporidian parasites of the genus Nosema, is considered a significant health concern for insect pollinators, including the economically important honeybee (Apis mellifera). Despite its acknowledged importance, the impact of this disease on honeybee survivorship remains unclear. Here, a standard laboratory cage trial was used to compare mortality rates between healthy and Nosema-infected honeybees. Additionally, a systematic review and meta-analysis of existing literature were conducted to explore how nosemosis contributes to increased mortality in honeybees tested under standard conditions. The review and meta-analysis included 50 studies that reported relevant experiments involving healthy and Nosema-infected individuals. Studies lacking survivorship curves or information on potential moderators, such as spore inoculation dose, age of inoculated bees, or factors that may impact energy expenditure, were excluded. Both the experimental results and meta-analysis revealed a consistent, robust effect of infection, indicating a threefold increase in mortality among the infected group of honeybee workers (hazard ratio for infected individuals = 3.16 [1.97–5.07] and 2.99 [2.36–3.79] in the experiment and meta-analysis, respectively). However, the meta-analysis also indicated high heterogeneity in the effect magnitude, which was not explained by our moderators. Furthermore, there was a serious risk of bias within studies and potential publication bias across studies. The findings underscore knowledge gaps in the literature. It is stressed that laboratory cage trials should be viewed as an initial step in evaluating the impact of Nosema on mortality and that complementary field and apiary studies are essential for identifying effective treatments to preserve honeybee populations.